Kitāb al-adwār fi ʼl-mūsīqī : Tarjuma-yi Fārsī bih inḍimām-i matn-i ʿArabi-yi ān - al-Urmawī, Ṣafī al-Dīn (Miras Maktoob, ISBN: 9789004365452., 2019)
In his younger years, the famous musician and theorist of music Ṣafī al-Dīn al-Urmawī (d. 683/1294) seemed destined for an administrative career. Having moved to Baghdad as an adolescent, he had received a first-class education, excelling in Arabic, calligraphy, and Shāfīʿī and comparative law especially. For a time he was a copyist in the library of the caliph al-Mustaʿṣim (reg. 640-56/1242-58) and a teacher of calligraphy. His talents as a lute-player and musician then led to a brilliant career at al-Mustaʿṣim's court. Under al-Mustaʿṣim he also held juridical office, while under the Mongols he was head of the chancery of Baghdad and supervisor of the religious endowments of Iraq. Administrative talents notwithstanding, it was in musical theory that Urmawī secured himself eternal fame. Innovative and concise, yet complete, his Kitāb al-adwār fi ʼl-mūsīqī became the most popular textbook in music for centuries. An undated, anonymous Persian translation is published here, together with the Arabic original.